The Effect of Procurement of Goods and Services on Budget Absorption of Regional Apparatus Units in Simeulue Regency - Junaidi, Novan; Aliamin, Aliamin; Abdullah, Syukriy (Riviera Publishing, 2023)
The purpose of this study was to examine the effect of planning for the procurement of goods/services, the competence of the manager of the procurement of goods/services and the application of e-procurement of the procurement of goods/services simultaneously on the absorption of the SKPK budget in Simeulue Regency. The entity that manages the procurement of goods/services within the local government of Simeulue Regency, which amounts to 43 SKPD. The sample in this study was determined by the Slovin equation as many as 77 people. The results of the study indicate that planning for procurement of goods and services, competence of managers of goods and services and the application of e-procurement affect budget absorption, planning for procurement of goods and services has a positive effect on budget absorption. increase budget absorption, the competence of goods/service managers has a positive effect on budget absorption, the better the competence of goods/services managers will increase budget absorption decisions, and the implementation of e-Procurement has an effect on budget absorption, the better the implementation of e-procurement will increase budget absorption. So that the results of this study can provide input for improving the procurement policy of goods/services at SKPK in Simeulue Regency.